Voluntary Disclosures and their Drivers: A Study of MDA Reports in India - Singla, Himani; Singh, Vijay (Organizations and Markets in Emerging Economies, 2024)
The aim of this study is to examine the impact of corporate characteristics on voluntary disclosures of management discussion and analysis (MD&A) reports in India. Using a formal tone, the data was extracted from the annual reports of the top 100 listed firms available on the CMIE Prowess database for seven years (2016–2022). After excluding 23 companies from the financial and insurance sector, a panel regression method with the assistance of Gretl software was employed to investigate the relationship between the Management Discussion and Analysis Disclosure Index (MDADI) for voluntary aspects and various corporate attributes, with a total of 490 firm years of balanced observations. In India, firms follow the mandatory compliance of the MD&A reports, but voluntary disclosures are somehow those which are not much emphasized but are a good indication of firm performance and their accountability towards their stakeholders (Mayew et al., 2015). Our empirical findings reveal that profitability as a proxy to firm performance has a significant positive relationship with MD&A voluntary disclosures. Further, an insignificant association between VDS (Voluntary Disclosure Score) and the board size, presence of independent directors and firm size was found. This indicates that firm performance plays a significant role in adding more voluntary disclosures in MD&A reports. The possible reason for this could be the use of “Management Impression Strategy” in the MD&A reports, which means managers disclose more only when the firm has earned more and use impressive language to attract stakeholders. The outcomes of this research offer valuable insights for regulators, policymakers, and listed companies in India, aiding in the enhancement of MD&A reporting quality. Additionally, this study provides a roadmap for future research on MD&A reporting quality and corporate attributes in other emerging countries that have similar regulatory frameworks. This paper makes a timely and pertinent contribution to the scholarly discourse by shedding light on the relationship between MD&A disclosures and firm attributes. Its findings provide valuable insights for both academia and industry.